EKSPLORASI KEARIFAN LOKAL DALAM LAGU HIP-HOP: STUDI ETNOPEDAGOGIK UNTUK PEMBELAJARAN BAHASA DAN BUDAYA BERBASIS DIGITAL BAGI MAHASISWA ASING - Dian Uswatun Hasanah; Rahmad Nanda Viky Susanto; Alif Aji Ramadhana (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society)
In this era of digital transformation, learning Indonesian for Foreign Speakers (BIPA) faces new challenges and opportunities. Foreign students need language learning experiences that incorporate local wisdom. Local wisdom-based BIPA learning is essential to help BIPA learners adapt to Indonesian culture and society. On the other hand, Indonesia's diverse cultural heritage has not been comprehensively utilized for BIPA learning, one of which is local hip-hop music. Hip-hop, as a contemporary music genre and easily accessible through digital platforms, can effectively communicate regional cultural narratives and values, making the learning process engaging and relevant for foreign students learning Indonesian. This study aims to explore the cultural values or local wisdom in hip-hop lyrics and relate them as teaching media for advanced BIPA learning. The research method used is descriptive qualitative and adopts an ethnopedagogical approach. The data sources are hip-hop lyrics developed in Central Java. Data was collected using content analysis techniques. Data validity and analysis techniques employed researcher triangulation and an interactive analysis model. The results of the study show that hip-hop songs are rich in local wisdom values that reflect the identity, philosophy, and spirit of the Javanese people. The local wisdom contained in these songs includes theological, ethical, aesthetic, logical, physical-physiological, and theological values. Hip-hop songs can be used as a means to promote local wisdom values and as a medium for language and cultural learning for foreign students. The results of this study contribute to facilitating the understanding of local wisdom in the social and cultural context of Indonesia in an enjoyable way for BIPA learners.